Geologi dan Petrografi Batuan Beku Desa Biluhu Barat, Gorontalo - Mohamad Nazer Ismail; Muh Kasim; Noviar Akase (Universitas Negeri Gorontalo, 2026)
Sulawesi Island has high geological complexity due to the collision of three major plates, yet detailed petrographic studies in Gorontalo Province, particularly in West Biluhu Village, remain limited. This study aims to map the geological conditions (geomorphology, stratigraphy, structure) at a scale of 1:5,000 and to identify igneous rock types using petrographic methods. The methods include field surveys, slope and joint measurements, and thin section analysis under a polarized microscope. The results show that the geomorphology consists of Volcanic Hill Unit and Denudational Volcanic Hill Unit. The stratigraphy from oldest to youngest is Andesite Unit and Dacite Unit, correlated with the Tinombo Formation (Eocene–Oligocene). The geological structure is characterized by tension joints with northeast–southwest and north–south orientations. Petrography reveals hydrothermally altered andesite (quartz-filled microfractures, embayed crystal) and dacite with interstitial quartz. This study is important as an integrated geological baseline data and an initial indication of mineralization potential in the area.